Evidence for the Gut Microbiota Short-Chain Fatty Acids as Key Pathophysiological Molecules Improving Diabetes - Viviani, Giorgio Luciano; Montecucco, Fabrizio; Sanguineti, Roberta; Puddu, Alessandra (Mediators of Inflammation, 2014)
In type 2 diabetes, hyperglycemia, insulin resistance, increased inflammation, and oxidative stress were shown to be associated with the progressive deterioration of beta-cell function and mass. Short-chain fatty acids (SCFAs) are organic fatty acids produced in the distal gut by bacterial fermentation of macrofibrous material that might improve type 2 diabetes features. Their main beneficial activities were identified in the decrease of serum levels of glucose, insulin resistance as well as inflammation, and increase in protective Glucagon-like peptide-1 (GLP-1) secretion. In this review, we updated evidence on the effects of SCFAs potentially improving metabolic control in type 2 diabetes.